Inhibition of UDP-glucose dehydrogenase by 6-Thiopurine and its oxidative metabolites: possible mechanism for its interaction within the bilirubin excretion pathway and 6-Thiopurine associated toxicity - Weeramange, Chamitha Janani (Kansas State University, 2018)
6-Thiopurine (6TP), or 6-mercaptopurine, is an actively prescribed drug in the treatment of acute lymphocytic leukemia since 1952. Although 6TP has beneficial and promising therapeutic uses, severe toxicities are associated with its use such as jaundice and hepatotoxicity. These toxicities are due to the higher level of accumulation of bilirubin within the body. The bilirubin pathway involves the conjugation of water-insoluble bilirubin to two equivalents of UDPglucuronic acid (UDPGA) forming the water-soluble and excretable bilirubin diglucuronide species. The glucuronidation of bilirubin is catalyzed by the UDP-glucuronosyl transferase (UGT) enzyme, and the formation of substrate UDPGA is catalyzed by the UDP-glucose dehydrogenase enzyme (UDPGDH).The therapeutic activity of 6TP comes from two main routes: methylation of the thiol of 6TP and formation of a deoxy-6-thioguanosine triphosphate mimic that is incorporated into DNA resulting in apoptosis. In conjugation to its therapeutic metabolism, there are also detoxification pathways operating simultaneously that significantly reduce its therapeutic activity. In this pathway, oxidative metabolites of 6TP such as 8-hydroxyl-6-thiopurine (6TP-8OH), 6-thioxanthine (6TX) and 6-thiouric acid (6TU) can be formed by xanthine oxidase. It has been observed that the body retains 6TU well beyond 24-hour post 6TP treatment. Therefore, we proposed that the observed toxicity from 6TP administration comes from either 6TP or its oxidative excretion metabolites’ ability to inhibit one or both enzymes (UDPGDH, UGT) in the bilirubin excretion pathway. To investigate the toxicity resulting from the 6TP administration about these two enzymatic steps, inhibition analysis of these oxidative metabolites on UDPGDH was assessed using a robust UV-Vis method. The inhibition profile made with regards to varying UDP-glucose showed weak to no inhibition of 6TP towards UDPGDH with a K[subscript i] of 288 μΜ. However, 6TU, (the primary oxidative metabolite which is oxidized at C2 and C8) has increased inhibition towards UDPGDH with K[subscript i] of 7 μΜ. Inhibition was also observed with 6TX (oxidized at C2) and 8-OH-6TP (oxidized at C8) with K[subscript i] values 54 and 14 μΜ, respectively. To further confirm the results of the UV-Vis assessment, inhibition studies were carried out using an HPLC method that was developed and validated to separate all the analytes in the UDPGDH catalyzed reaction. Inhibition studies were performed via the HPLC method showed K[subscript i] values of 105 μΜ and 5 μΜ for 6TP and 6TU, respectively, towards UDPGDH. To assess the inhibition studies towards the UGT enzyme, an HPLC method was developed for the simultaneous determination of bilirubin and its mono/diglucuronides. The inhibition studies were carried to assess the formation of glucuronides and consumption of UDPGA in the presence of the inhibitors using the HPLC method developed. Neither 6TP nor 6TU were shown to inhibit UGT. Also, inhibition studies were carried out in vivo animal model, which further confirmed that 6TP and 6TU do inhibit UDPGDH, but no effect on UGT activity. With these results, we discovered that both 6TP and its oxidative metabolites inhibit UDPGDH. Furthermore, it was observed that C2 and C8 positions of 6TP are important for the toxicity towards UDPGDH. With the goal of developing a single multi-enzymatic assay, another HPLC method was developed to assess the UDPGDH and UGT catalyze reactions together. This method can be used as a standard method to assess interference of any molecule on bilirubin excretion. Given the findings in this study, efforts are being directed towards the synthesis of 8-substituted 6TP analogs that are proposed to retain its therapeutic efficacy but have limited to no toxicity.
Keywords: UDPG; UDPGA; UDPGDH; UGT1A1; Bilirubin; Bilirubin glucuronide